2003
DOI: 10.1080/01926230390242016
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Nasal Lesions in F344/N Rats Following Chronic Inhalation Exposure to Naphthalene Vapors

Abstract: Naphthalene administered by inhalation at concentrations of 10, 30, or 60 ppm for 6 hours per day, 5 days per week for 105 weeks caused nonneoplastic and neoplastic effects in nasal respiratory and olfactory regions of male and female F344/N rats. Non-neoplastic nasal effects were characterized by an increase in the incidence and severity of a complex group of lesions, including atypical hyperplasia, atrophy, chronic inflammation, and hyaline degeneration of olfactory epithelium; hyperplasia, squamous metapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…A partly genotoxic mode of action cannot be ruled out, as may be indicated by absence of nasal tumors in mice chronically exposed to 10 or 30 ppm naphthalene, despite evidence of nasal irritation, nasal respiratory epithelium hyperplasia, and nasal olfactory-epithelium metaplasia in these mice (NTP, 1992;Abdo et al, 1992). However, in contrast to the spectrum of non-neoplastic nasal lesions including atypical, strongly basophilic, multi-focal and/or "unusual" types-some involving moderate to severe atrophy-detected in naphthaleneexposed rats (Long et al, 2003) discussed above, average severity scores reported for nonneoplastic nasal lesions that occurred in similarly exposed male and female mice all fell within a "minimal" to "mild" range, below scores ≥3 associated with "moderate" or "severe" toxicity (Abdo et al, 1992). The combined rodent bioassay evidence therefore indicates a likely predominant cytotoxic mode of action contributing to the nasal tumors observed in naphthalene-exposed rats.…”
Section: Scientific Claims With High Confidencementioning
confidence: 83%
See 2 more Smart Citations
“…A partly genotoxic mode of action cannot be ruled out, as may be indicated by absence of nasal tumors in mice chronically exposed to 10 or 30 ppm naphthalene, despite evidence of nasal irritation, nasal respiratory epithelium hyperplasia, and nasal olfactory-epithelium metaplasia in these mice (NTP, 1992;Abdo et al, 1992). However, in contrast to the spectrum of non-neoplastic nasal lesions including atypical, strongly basophilic, multi-focal and/or "unusual" types-some involving moderate to severe atrophy-detected in naphthaleneexposed rats (Long et al, 2003) discussed above, average severity scores reported for nonneoplastic nasal lesions that occurred in similarly exposed male and female mice all fell within a "minimal" to "mild" range, below scores ≥3 associated with "moderate" or "severe" toxicity (Abdo et al, 1992). The combined rodent bioassay evidence therefore indicates a likely predominant cytotoxic mode of action contributing to the nasal tumors observed in naphthalene-exposed rats.…”
Section: Scientific Claims With High Confidencementioning
confidence: 83%
“…NTP rat nasal tumor occurrence was greatly enhanced, if not enabled, by adjacent, histologically related focal cellular proliferation Histopathology findings obtained from the NTP (2000) bioassay strongly suggest that nasal tumor formation in rats chronically exposed to naphthalene by inhalation was associated with, if not enabled solely, by chronic tissue damage and associated regenerative and focal hyperplasia. The extent of chronic nasal cytotoxicity and hyperplasia detected in nearly 100% of all exposed animals (regardless of dose group) was described by Long et al (2003) as follows (bold added):…”
Section: Scientific Claims With High Confidencementioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory mucosal toxicity and carcinogenicity occur in rats treated with the phosphodiesterase inhibitor RP 73401, but not mice or dogs (Pino et al, 1999). Similarly, naphthalene is carcinogenic in the rat olfactory mucosa, but not the mouse (National Toxicology Program, 1992;Long et al, 2003). Coumarin caused olfactory mucosal degeneration in both rats and mice; however, rats were more sensitive than mice.…”
Section: Discussionmentioning
confidence: 99%
“…"Atypical" hyperplasia and olfactory neuroblastomas were observed in rat but not mouse olfactory epithelium (nearly 100% at all doses in rat)� As shown in Table 3, the mouse nasal data are categorized as "ad hoc assumptions required"; that is, if chronic inflammation and regenerative hyperplasia are key events in the naphthalene MoA, and these key events occur in mouse nasal tissue but do not lead to tumor formation, ad hoc assumptions are necessary to explain this observation� Hyperplasia is defined as an increase in the number of normal cells in a normal arrangement within a tissue; it exhibits a normal growth pattern and maturation sequence, and is not generally considered "preneoplastic" (Eustis, 1989)� Atypical hyperplasia (dysplasia), on the other hand, is defined as a proliferation of cells characterized by cellular atypia, alteration in the maturation sequence, or abnormal differentiation of cells within a tissue, and frequently indicates the emergence of a population of cells that may become cancerous (Eustis, 1989)� As discussed in Bogen et al� (2008) and Long et al� (2003), atypical hyperplasia as observed in the rat tumor assay was considered "an unusual proliferative lesion… [and] may represent a precursor for nasal olfactory carcinogenesis� " As shown in Table 3, the rat nasal data provide "some evidence" that CYP2F-induced chronic inflammation and regenerative hyperplasia are key events in the naphthalene MoA, again with the question as to the potential involvement of other CYPs or other metabolic enzymes� However, the olfactory epithelial data provide strong evidence that, regardless of the CYP involved in the primary metabolism of naphthalene, "atypical" hyperplasia may be the key event necessary for carcinoma formation�…”
Section: Is There Further Metabolism Of the Naphthalene Epoxide In Thmentioning
confidence: 99%